PERAN IKLIM ORGANISASI DALAM MENINGKATKAN MOTIVASI KERJA KARYAWAN PADA PDAM GIRI MENANG MATARAM - Cahyadi, Irwan; Anggriani, Rini; Febriana, Widia; Abdurrahman, Abdurrahman; Roodhi, Mohammad Najib (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
The role of organizational climate in an organization is very important, if the organizational climate does not support the work motivation will be lost, and it will result in imperfect work results and the results in providing services to customers (consumers) become unsatisfactory. The purpose of this study is to determine the role of organizational climate factors consisting of psychological dimensions, structural dimensions, social dimensions, and bureaucratic dimensions in increasing the work motivation of PDAM Giri Menang Mataram employees. This type of research is included in associative research which uses a sample survey method in data collection. The analytical tool used is t test analysis at 5% alpha. Based on the results of the t test, it is known that organizational climate factors consisting of psychological dimensions, structural dimensions, social dimensions, and bureaucratic dimensions have a significant effect on increasing the work motivation of PDAM Giri Menang Mataram employees.